2008
DOI: 10.2337/dc07-0632
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Diabetic Retinopathy

Abstract: OBJECTIVE -Homocysteine is an emerging risk factor for cardiovascular and nondiabetic ocular vaso-occlusive diseases. However, studies of the relationship between homocysteine and diabetic retinopathy have reported inconsistent results. The purpose of this study was to evaluate the relationship between plasma total homocysteine concentration and diabetic retinopathy. RESEARCH DESIGN AND METHODS -We assessed the homocysteine-retinopathy relationship in 168 men and women with type 2 diabetes in a community-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 29 publications
(11 reference statements)
4
60
0
4
Order By: Relevance
“…Rather unexpectedly, it was not significantly related to history of macroangiopathy in our patients. Our finding is compatible with the data presented by recent studies which inferred that elevated HC was a risk factor for retinopathy [11,22,23]. Nevertheless, it should be noted that plasma HC concentration was only marginally higher (P =0.05) in the metformin users than the non-metformin users and prevalence of retinopathy was not significantly different between the two groups.…”
Section: Disclosuressupporting
confidence: 82%
“…Rather unexpectedly, it was not significantly related to history of macroangiopathy in our patients. Our finding is compatible with the data presented by recent studies which inferred that elevated HC was a risk factor for retinopathy [11,22,23]. Nevertheless, it should be noted that plasma HC concentration was only marginally higher (P =0.05) in the metformin users than the non-metformin users and prevalence of retinopathy was not significantly different between the two groups.…”
Section: Disclosuressupporting
confidence: 82%
“…6,7 Oküler hastalıklardan ise lens ektopisi, optik atrofi, retinal arter ve ven tıkanıklığı, yaşa bağlı maküla dejenerasyonu ve DR ile ilişkili olduğu bildirilmektedir. [8][9][10][11][12] Literatürde diabetik hastalarda plazma homosistein düzeylerinin değerlendirildiği çalışmalarda çelişkili sonuçlar bildirilmektedir, normal popülas-yondan yüksek, düşük veya benzer düzeyde göste-rildiği çalışmalar mevcuttur. [13][14][15] Çalışmamızın amacı, diabetik hastalarda plazma homosistein düzeyle-rini sağlıklı bireylerle karşılaştırmak ve retinopatinin şiddeti ile ilişkisini değerlendirmektir.…”
Section: Sonuçunclassified
“…Many studies since have confirmed this association for type 2 diabetes mellitus as well. [57][58][59] It is also true that severity of retinopathy correlates strongly with Hcy level, independent of glycaemic control. 60 Higher Hcy levels are observed in individuals with proliferative retinopathy compared to non-proliferative retinopathy, even though in both instances the levels are significantly elevated compared to control.…”
Section: Diabetic Retinopathymentioning
confidence: 99%